Effects of non-neurological complications on traumatic brain injury outcome - Meyer, Kimberly S (BioMed Central, 2012)
Traumatic brain injury (TBI) affects over 1.5 million Americans annually and consumes a significant amount of healthcare dollars. Identification of complications and factors that impact recovery from TBI is important in improving outcome and allocating appropriate resources. Understanding the role of non-neurologic complications such as sepsis, acute kidney injury, and respiratory problems on TBI outcome and mortality is critical.